2016
DOI: 10.15252/msb.20156720
|View full text |Cite
|
Sign up to set email alerts
|

The interdependence of transcript and protein abundance: new data–new complexities

Abstract: The relative contribution of transcriptional and translational regulation in gene expression control has been intensely debated and remains a challenging question. Recent reports have suggested that protein abundance in mammalian cells is primarily controlled at the transcript‐level. In their recent work, Cheng et al (2016) determined the proteomic and transcriptomic changes in cells responding to endoplasmic reticulum (ER) stress. Their analyses indicate that the ER stress response is significantly controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
0
24
1
Order By: Relevance
“…The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). Likewise, our comparative 2DE analysis showed that post-transcriptional regulation has a large impact on the expression of functional proteins during xylem vessel cell differentiation.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). Likewise, our comparative 2DE analysis showed that post-transcriptional regulation has a large impact on the expression of functional proteins during xylem vessel cell differentiation.…”
Section: Resultsmentioning
confidence: 62%
“…Recent comparative studies between proteomic and transcriptomic data revealed low correlations for a certain number of genes (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Results demonstrated that there was a low correlation between the proteome and transcriptome data, suggesting that post-transcriptional gene regulation influences different biological pathways and secondary metabolite gene clusters. Liu and Aebersold (2016) reported that it is highly unlikely that cells would divert resources towards such elaborate regulatory mechanisms at both the transcript and protein levels if they could have simply controlled protein synthesis via strict transcriptional regulation, as predicted by the central dogma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proteomics can be used to compare changes in levels of many proteins under particular genetic and environmental conditions. However, proteomic studies provide information on post-translational modifications, which cannot be obtained from mRNA expression profiles; these have proven critical to our understanding of proper physiological protein function, translocation, and subcellular localization (Bastiaanse et al 2014;Liu and Aebersold 2016). Understanding the mutual regulatory interactions between transcriptome and proteome necessitates an approach that encompasses the simultaneous monitoring of expression at both the RNA and protein levels (Cheng et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging theme in these studies is ability of transcript abundance variation to only partially explain protein abundance variation [44,45,46]. The degree of contribution to gene expression regulation by transcription and translation varies substantially in different biological systems.…”
Section: Understanding All Levels Of Gene Expression Regulationmentioning
confidence: 99%